Production of low‐Cs+ rice plants by inactivation of the K+ transporter OsHAK1 with the CRISPR‐Cas system. (11th August 2017) - Nieves‐Cordones, Manuel; Mohamed, Sonia; Tanoi, Keitaro; Kobayashi, Natsuko I.; Takagi, Keiko; Vernet, Aurore; Guiderdoni, Emmanuel; Périn, Christophe; Sentenac, Hervé; Véry, Anne‐Aliénor
Summary: The occurrence of radiocesium in food has raised sharp health concerns after nuclear accidents. Despite being present at low concentrations in contaminated soils (below μm ), cesium (Cs + ) can be taken up by crops and transported to their edible parts. This plant capacity to take up Cs + from low concentrations has notably affected the production of rice ( Oryza sativa L.) in Japan after the nuclear accident at Fukushima in 2011. Several strategies have been put into practice to reduce Cs + content in this crop species such as contaminated soil removal or adaptation of agricultural practices, including dedicated fertilizer management, with limited impact or pernicious side‐effects. Conversely, the development of biotechnological approaches aimed at reducing Cs + accumulation in rice remain challenging. Here, we show that inactivation of the Cs + ‐permeable K + transporter OsHAK1 with the CRISPR‐Cas system dramatically reduced Cs + uptake by rice plants. Cs + uptake in rice roots and in transformed yeast cells that expressed OsHAK1 displayed very similar kinetics parameters. In rice, Cs + uptake is dependent on two functional properties of OsHAK1: (i) a poor capacity of this system to discriminate between Cs + and K + ; and (ii) a high capacity to transport Cs + from very low external concentrations that is likely to involve an active transport mechanism. In an experiment with a Fukushima soil highly contaminated with 137 Cs +, plants lacking OsHAK1 function displayed strikingly reduced levels of 137 Cs + in roots and shoots. These results open stimulating perspectives to smartly produce safe food in regions contaminated by nuclear accidents. Significance Statement: After nuclear accidents, production of safe food is challenged by the presence of radiocesium in the environment, since crops take up cesium (Cs + ) from contaminated soils and transport it to edible parts. Here we report that inactivation with the CRISPR‐Cas system of the main transporter that takes up Cs + from the soil in rice, OsHAK1, leads to strikingly reduced levels of 137 Cs + in shoots when grown in highly contaminated soil from Fukushima.